[Ekslibris] Anna Tomasz Daniel - Langner, Wiktor Zbigniew (1906-1985).; Daniel, Anna.; Daniel, Tomasz (1983)
Na trzech prostokątach napis: Anna Tomasz Daniel, pod wyobrażeniem ołówkiem autograf artysty i data.
Keywords: Ekslibrisy -- Polska -- 1970-2000.